Mechanisms of Berberine (Natural Yellow 18)–Induced Mitochondrial Dysfunction: Interaction with the Adenine Nucleotide Translocator - Pereira, Cláudia V. (2008)
Berberine [Natural Yellow 18, 5,6-dihydro-9,10-dimethoxybenzo(g)-1,3-benzodioxolo (5,6-a) quinolizinium] is an alkaloid present in plants of the Berberidaceae family and used in traditional Chinese and North American medicine. We have previously demonstrated that berberine causes mitochondrial depolarization and fragmentation, with simultaneous increase in oxidative stress. We also demonstrated that berberine causes an inhibition of mitochondrial respiration and a decrease on calcium loading capacity through induction of the mitochondrial permeability transition (MPT). The objective of the present work is to investigate a common target for both induction of the MPT and inhibition of respiration. The hypothesis is that berberine induces the MPT through interacting with the adenine nucleotide translocator (ANT). By measuring induction of the MPT through increased mitochondrial swelling, membrane depolarization and loss of calcium retention, we observed that the effects of berberine were not inhibited by bongkrekic acid although adenosine diphosphate (ADP)/oligomycin completely prevented the MPT. Also, we observed that berberine increased the depolarization effect of oleic acid on liver mitochondria. The initial depolarization observed when berberine is added to mitochondria was not affected by ANT inhibitors. Taken together, we propose that berberine acts on the ANT, altering the binding of the protein to bongkrekic acid but not to cyclosporin A or ADP. It is also clear that the membrane potential is required for berberine effects, most likely for allowing for its mitochondrial accumulation. Mitochondrial effects of berberine can be relevant not only for its proposed antitumor activity but also for the assessment of its organ toxicity, depending on factors such as tissue accumulation or delivery.